Determining the flocculation point of asphaltenes combining ultrasound and electrochemical impedance spectroscopy. (1st April 2019) - Moncada, Jorge; Schartung, David; Stephens, Natalie; Oh, Tae-Sik; Carrero, Carlos A.
Graphical abstract: Abstract: The characterization of asphaltenes in heavy crude oil remains relevant as continuous extraction of conventional oil pushes industries to seek oil from new, unconventional sources. Unconventional crude oil contains a high concentration of asphaltenes, resulting in a very dense (22.3-10 °API) and viscous substance, which makes the handling and processing of this type of petroleum more challenging. The flocculation of asphaltenes is still a challenge to address during crude oil production, transportation, blending, and processing. Therefore, understanding the phase behavior of asphaltenes as well as their stability and physicochemical properties demands new and more practical characterization techniques capable of providing new insights into the asphaltene flocculation process. Current characterization techniques used to determine the flocculation point of asphaltenes in crude oil are primarily based on optical techniques and ex-situ methodologies. In this work, we propose, investigate, and provide preliminary results on a new approach aimed to determine the flocculation point of asphaltenes using electrochemical impedance spectroscopy (EIS) assisted by ultrasound (US). Our results show that the asphaltene flocculation process is significantly influenced by using US pulses, which promote the disaggregation of asphaltenes, thus allowing the determination of the flocculation point of asphaltenes via EIS.